(Re)presenting the female form: shaped by artists Nelson Mukhuba, Noria Mabasa and Johannes Maswanganyi - Parry, Melissa (My University, 2016)
No abstract
History of Art Masters of Art by Course Work and Research Report
Keywords: Mukhuba, Nelson; Mabasa, Noria,|d1938-; Maswanganyi, Johannes; Artists--South Africa; Artists--Black--South Africa; Sculptors--South Africa